Insufficiency of Thyroid Hormone in Frog Metamorphosis and the Role of Glucocorticoids - Sachs, Laurent M.; Buchholz, Daniel R. (Frontiers in Endocrinology, 2019)
Thyroid hormone (TH) is the most important hormone in frog metamorphosis, a developmental process which will not occur in the absence of TH but can be induced precociously by exogenous TH. However, such treatments including in-vitro TH treatments often do not replicate the events of natural metamorphosis in many organs, including lung, brain, blood, intestine, pancreas, tail, and skin. A potential explanation for the discrepancy between natural and TH-induced metamorphosis is the involvement of glucocorticoids (GCs). GCs are not able to advance development by themselves but can modulate the rate of developmental progress induced by TH via increased tissue sensitivity to TH. Global gene expression analyses and endocrine experiments suggest that GCs may also have direct actions required for completion of metamorphosis independent of their effects on TH signaling. Here, we provide a new review and analysis of the requirement and necessity of TH signaling in light of recent insights from gene knockout frogs. We also examine the independent and interactive roles GCs play in regulating morphological and molecular metamorphic events dependent upon TH.